The effects of individual differences and visual instructional aids on disorientation, learning performance and attitudes in a Hypermedia Learning System - Ruttun, Rishi D.; Macredie, Robert D. (Computers in Human Behavior, 2012)
Abstract: Research suggests that certain visual instructional aids can reduce levels of disorientation and increase learning performance in, and positive attitudes towards, HLS for learners with specific individual differences. However, existing studies have looked at only one or two individual differences at a time, and/or considered only a small number of visual instructional aids. No study has considered the impact of the three most commonly studied individual differences – cognitive style, domain knowledge and computer experience – on learning performance, disorientation and attitudes in a HLS incorporating a full range of visual instructional aids. The study reported here addresses this shortcoming, examining the effects of, and between, these three individual differences in relation to learning performance, disorientation and attitudes in two HLS versions: one that incorporated a full set of visual instructional aids and one that did not. Significant effects were found between the three individual differences with respect to disorientation, learning performance and attitudes in the HLS that provided no instructional aids, whereas no such effects were found for the other HLS version. Analysis of the results led to a set of HLS design guidelines, presented in the paper, and the development of an agenda for future research. Limitations of the study and their implications for the generalizability of the findings are also presented.